Simulation Of Flood Inundation Map Associated With Sediment Transport For Sungai Pahang - Chang, Chun Kiat (2018)
Flood disasters are a major cause of fatalities and economic losses. Several studies indicate that global flood risk is currently increasing. Rapid urbanisation has accelerated impact on the catchment hydrology and geomorphology. When landuse and land cover change as a result of development or human activities, such as logging which takes place in river catchment areas, a dramatic increase in the surface runoff and higher sediment yield are expected. The present study can be divided into four (4) main parts. The first part is to carry out trend analysis using Mann-Kendall test for the annual rainfall time series data. The results demonstrate that increasing trends were detected for eleven (11) rainfall stations while four (4) stations showing decreasing trends in Sungai Pahang river basin. The second part attempts to give an overview of the channel changes and sediment transport phenomena in Sungai Pahang including bed material movement from the upstream of Sungai Pahang to the river mouth at Pekan. River geometry survey associated with the spatial variation in sediment transport has confirmed that changes in river bed profile occurred due to erosion or deposition along Sungai Pahang. The sediment distribution size for Sungai Pahang was found to be made up of very coarse sand and gravel after December 2014 flood. A rainfall-runoff model is developed and implemented for Sungai Pahang river basin. Performance evaluation of the InfoWorks PDM model was moderately successful in reproducing 2003 and 2012 to 2014 hydrographs covering both low and high flow, which have been the emphasis of the third part of this research. The fourth part is intended to deal with flood simulation using InfoWorks RS with the consideration of sediment transport modeling. The flood inundated area has been estimated based on the input design hydrograph of the 100-year annual recurrent interval and storm duration of 8 days. Peak water surface and channel bed changes for Sungai Pahang indicated that the maximum flood level with and without sediment transport modeling has a difference of at least 0.30m. The flooded area was identified to increase by 306.84km² (30.21%) from the simulations results without sediment transport compared to flood simulations with sediment transport. As a result, the current study shows that it is essential to take into account the sediment movement along the river channel for the prediction of flood inundation areas in order to produce digital flood maps.